2020
DOI: 10.1093/rheumatology/keaa215
|View full text |Cite
|
Sign up to set email alerts
|

Association between age at disease onset of anti-neutrophil cytoplasmic antibody–associated vasculitis and clinical presentation and short-term outcomes

Abstract: Objectives ANCA-associated vasculitis (AAV) can affect all age groups. We aimed to show that differences in disease presentation and 6 month outcome between younger- and older-onset patients are still incompletely understood. Methods We included patients enrolled in the Diagnostic and Classification Criteria for Primary Systemic Vasculitis (DCVAS) study between October 2010 and January 2017 with a diagnosis of AAV. We divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…There was no difference in other clinical manifestations, nor in FFS, between the two groups. Similar findings have been described in other studies [6,7]. The present cohort, both age groups included, also had characteristics similar to two large French (n = 162 patients, mean age 61) and American cohorts (n = 347, mean age 58) [24,26].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was no difference in other clinical manifestations, nor in FFS, between the two groups. Similar findings have been described in other studies [6,7]. The present cohort, both age groups included, also had characteristics similar to two large French (n = 162 patients, mean age 61) and American cohorts (n = 347, mean age 58) [24,26].…”
Section: Discussionsupporting
confidence: 89%
“…The peak incidence rate of AAV is estimated at 65-75 years, and remains elevated even after 75 years of age [2][3][4]. Older patients have more frequently a diagnosis of MPA characterized by more frequent anti-myeloperoxidase antibody (MPO-ANCA) positivity, kidney involvement, and less ear nose throat (ENT) involvement as compared with younger AAV patients [5][6][7]. Induction treatment of AAV is efficient among older patients and remission rates are estimated between 74% and 97% [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with our previous report that during the lockdown period in March and April 2020, an incidence-shift with a COVID-19 gap of non-diagnosed AAV based on renal biopsy was followed by a postlockdown phase in subsequent months with a compensatory increased incidence rate ( Hakroush and Tampe, 2021 ). According to the literature, various kidney diseases are preceded by a prodromal phase characterized by constitutional symptoms ( Monti et al, 2020 ). Diagnostic delay at this stage is common and has been demonstrated to be associated with mortality and end-stage renal disease ( Koldingsnes and Nossent, 2002 ; Houben et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, AAV is preceded by a prodromal phase characterised by constitutional symptoms that pursue a waxing and waning course. 3 Diagnostic delay at this stage is common, and it has been demonstrated that a longer prodromal phase associated with mortality 4 5 and end-stage renal disease. 5 AAV should therefore always be considered as a possible differential diagnosis in patients with constitutional symptoms without a clear explanation.…”
mentioning
confidence: 99%